Bad-Faith Practices in E-Commerce Standard Clauses and Their Impact on Consumer Protection - Rahma, Deva Aurelia; Sulastri Sulastri (JURNAL USM LAW REVIEW, 2025)
This study examines consumer legal protection concerning the application of standard clauses in e-commerce electronic agreements, which often create an imbalance of bargaining power between business actors and consumers. The research is motivated by the persistence of unfair standard clauses resulting from weak supervision and ineffective law enforcement, enabling bad faith practices by business actors. This study employs a normative juridical method using statutory, conceptual, and case study approaches to assess the effectiveness of consumer protection regulations in electronic transactions. The findings indicate that although courts tend to uphold business actors’ responsibility to provide honest and transparent information, the absence of effective preventive supervision mechanisms continues to undermine consumer protection. The novelty of this research lies in proposing a preventive oversight model through the pre-approval of standard clauses by competent authorities prior to the enforcement of electronic agreements, contrasting with prior studies that predominantly adopt reactive and evaluative approaches. This study concludes that implementing a pre-approval mechanism is essential to foster a fair and transparent e-commerce business environment and to strengthen comprehensive consumer protection in Indonesia.